Bridging Traditional Language Pedagogy and AI: Lessons from Arabic Language Programs in Indonesia - Mustar; Raswan; Chabib Uluum, Dina; Tamami, Keysa; Bin Mohamad, Muhammad Ramdhan (Institut Agama Islam Negeri Curup, 2025)
This article examines the integration of traditional pedagogical approaches in Arabic language teaching with emerging artificial intelligence (AI) technologies within Islamic higher education institutions in Indonesia. The study was conducted at two state Islamic universities using a descriptive qualitative approach, with lecturers serving as the primary participants. The findings revealed that conventional learning methods, such as nahwu-sharf and qirā’ah al-kutub, remained the core instructional foundation. However, an increasing number of lecturers had begun incorporating AI-based tools, including chatbots, speech-recognition applications, and adaptive online learning platforms. Overall, lecturers perceived AI as a supportive complement rather than a substitute, one that could enhance students’ learning experiences. At the same time, concerns persisted regarding the accuracy of AI-generated content and its alignment with Islamic values. This study highlights the need for an integrative instructional model that leverages the strengths of classical methods while harnessing AI’s potential to create contextual, moderate, and responsive learning experiences suited to contemporary educational demands. With adequate policy support and ongoing lecturer capacity building, the synergy between traditional pedagogy and AI is expected to accelerate the transformation of Arabic language education in Islamic higher education settings.